Best practice quality function deployment (QFD) cases - Hunt, Robert A.; Killen, Catherine P. (International Journal of Quality & Reliability Management., 2004)
To provide an advanced product definition methodology based on quality function deployment (QFD) principles to identify minimize the risks of project failures due to failure to align with the voice of the business. The methodology was developed by reviewing current design product definition and QFD tools and then applied to a number of industry-based design projects in academia as well as an in-depth case study at one industry organization. The tool has been well accepted for its ease and approach in both industry and academic environments and already used to help guide project management. The.